Life Cycle Dynamics of a Key Marine Species Under Multiple Stressors - Otto, Saskia A.; Niiranen, Susa; Blenckner, Thorsten; Tomczak, Maciej T.; Müller-Karulis, Bärbel; Rubene, Gunta; Möllmann, Christian (Frontiers in Marine Science, 2020)
Identifying key indicator species, their life cycle dynamics and the multiple driving forces they are affected by is an important step in ecosystem-based management. Similarly important is understanding how environmental changes and trophic interactions shape future trajectories of key species with potential implications for ecosystem state and service provision. We here present a statistical modelling framework to assess and quantify cumulative effects on the long-term dynamics of the copepod Pseudocalanus acuspes, a key species in the Baltic Sea. Our model integrates linear and non-linear responses to changes in life stage density, climate and predation pressure as well as stochastic processes. We use the integrated life cycle model to simulate copepod dynamics under a combination of stressor scenarios and to identify conditions under which population responses are potentially mitigated or magnified. Our novel modelling approach reliably captures the historical P. acuspes population dynamics and allows us to identify females in spring and younger copepodites in summer as stages most sensitive to direct and indirect effects of the main environmental stressors, salinity and temperature. Our model simulations furthermore demonstrate that population responses to stressors are dampened through density effects. Multiple stressor interactions were mostly additive except when acting on the same life stage. Here, negative synergistic and positive dampening effects lead to a lower total population size than expected under additive interactions. As a consequence, we found that a favorable increase of oxygen and phosphate conditions together with a reduction in predation pressure by 50% each could counteract the negative effect of a 25% decrease in salinity by only 6%. We therefore advocate that management strategies aimed to mitigate the effects of climate-related stressors should target life stage not affected by climate for more effective and predictable results. Our modelling framework can help here as simple tool for species with a discrete life cycle to explore stressor interactions and the safe operating space under future climate change.